A new mud shrimp of the genus Paragourretia Sakai, 2004, from the Gulf of Mexico (Crustacea: Decapoda: Ctenochelidae) - Felder, Darryl L.; Dworschak, Peter C. (Zootaxa, 2023)
A new western Atlantic member of the ctenochelid genus Paragourretia Sakai, 2004 is described to accommodate a single unique specimen collected by dredge on muddy rubble substrates of the continental shelf in the southwestern Gulf of Mexico. Paragourretia sandrae n. sp. closely resembles Paragourretia biffari (Blanco Rambla & Liñero Arana, 1994), another regionally reported species for which photographs and additional illustrations are herein provided. While P. biffari and P. sandrae n. sp. are similar in habitus and known habitat to the more commonly encountered confamilial Dawsonius latispina (Dawson, 1967), the third maxillipeds in Paragourretia bear distinct exopods that are absent in Dawsonius Manning & Felder, 1991. As in eight other world congeners, P. sandrae n. sp. differs from both P. biffari and Dawsonius in lacking triangular ventrolateral projections on the sixth pleomere. It is further distinguished from P. biffari by lacking a distinctly incised notch in the anterodistal margin of the uropodal exopod and by absence of a median terminal spine on the telson. Additional sequence-quality specimens of P. sandrae n. sp. are required to clarify its relationships within the polyphyletic genus Paragourretia on a molecular genetic basis.